The Matthew effect in the casino industry: A dynamic performance perspective. (June 2017) - Liu, Day-Yang; Wu, Ya-Chiang; Lu, Wen-Min; Lin, Cheng-Hsien
Abstract: The Matthew effect was first coined by sociologist Merton and takes its name from a verse in the biblical Gospel of Matthew ("unto them that hath shall be given, from them that hath not shall be taken away"). This paper explores whether company size confers a Matthew effect that is able to reduce losses during severe economic downturns. First, this study employs the dynamic slack-based measure model to evaluate the performance of U.S. casino companies (CCs) for the period from 2004 to 2013. Panel data regression is next applied to investigate the impact of Matthew effect on operating performance. Several empirical results are as follows: CCs are generally more efficient prior to a financial crisis than afterward; post-financial crisis CCs suffer from the Matthew effect. Furthermore, large-size CCs are more efficient than small-size CCs; and CCs with conglomerate structures perform better post-crisis than others. The findings of this study could help policy makers in the America casino industry formulate and implement policies involving the Matthew effect and enable corporate policy makers to improve their corporate performance efficiency.